Jenis-Jenis Jamur Makroskopis di Kawasan Hutan Desa Namo Kecamatan Kulawi Kabupaten Sigi - Ria, Amanda; Alibasyah, Lestari M.P.; Aan, Febriawan; Astija, Astija; Buntu, Amalia; Mawaddah, Hayyatun (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify the types of macroscopic fungi found in the forest area of Namo Village, Kulawi Subdistrict, Sigi Regency. The research employed an exploratory method with a free collection sampling technique. Sampling was conducted at three different stations: forest area, plantation, and residential settlement. The observational data were analyzed descriptively and identified using reference books, scientific publications, and the Google Lens application. The results of the study revealed a total of 30 species of macroscopic fungi, classified into two phyla, namely Basidiomycota and Ascomycota, encompassing 4 classes, 7 orders, and 16 families. The Basidiomycota phylum dominated with the highest number of species, comprising 21 genera, 14 families, and 5 orders. In contrast, the Ascomycota phylum consisted of only 2 genera, 2 families, and 2 orders. These findings indicate a high diversity of macroscopic fungi, highlighting the potential of these biological resources for educational purposes and further scientific research.